PEMBELAJARAN STAD PADA MATERI IPA BERBANTUAN MEDIA RAMAH LINGKUNGAN DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - Winda Febrianti; Bambang Subali; Tri Suminar; Nuni Widiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Class 5 students at SDN Adiwerna 01 experience learning difficulties. Especially in science material about the human digestive organ system. This is due to the minimal variety of teaching aids and learning models that are able to help students understand the learning material. This research aims to describe the application of STAD learning assisted by environmentally friendly teaching aids in improving the learning outcomes of elementary school students. This research method is quantitative with a quasi-experimental design. The results of this research show that once implemented, the STAD model assisted by environmentally friendly teaching aids can improve student learning outcomes. This is indicated by the N-Gain value in the experimental class being higher than the control class. In the experimental class, the average N-Gain test result was 0.7 with high criteria, while in the control class the average N-Gain test result was 0.3 with low criteria. Based on this, it proves that the results of research on STAD learning using environmentally friendly teaching aids are able to change students' grades in the material on the human digestive organ system in class 5 at SDN Adiwerna 01 for the better. Peserta didik Kelas 5 SDN Adiwerna 01 mengalami kesulitan belajar. Terutama pada pokok bahasan IPA sistem organ pencernaan manusia. Hal tersebut disebabkan minimnya jenis media pembelajaran dan model pembelajaran yang dimanfaatkan guru dalam menyampaikan materi ajar. Penelitian ini ditujukan untuk mendeskripsikan penerapan model pembelajaran STAD berbantuan media pembelajaran ramah lingkungan dalam meningkatkan hasil belajar peserta didik SD. Metode penelitian berupa kuantitatif menggunakan desain quasi eksperimen. Hasil penelitian ini menunjukkan nilai N-Gain di kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Pada kelas eksperimen menunjukkan hasil uji N-Gain rata-rata sebesar 0,7 dengan kriteria tinggi sedangkan pada kelas kontrol hasil uji N-Gain rata-rata sebesar 0,3 dengan kriteria rendah. Berdasarkan data tersebut membuktikan bahwa setelah diimplementasikan, model STAD berbantuan media pembelajaran ramah lingkungan mampu menjadikan nilai peserta didik naik dalam materi sistem organ pencernaan manusia pada kelas 5 SDN Adiwerna 01.